Development of Pedagogic Competencies of Prospective Penjas Teachers through Traditional Game Modification Training as Active Learning Media - Novita Nur Synthiawati; Rahayu Prasetyo; Arsika Yunarta (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Abstract: This community service activity aims to improve the pedagogic competence and creativity of prospective Physical Education teachers in modifying traditional games as active learning media. The program is carried out on students of the Physical Education Study Program, University of PGRI Jombang who based on the results of the initial assessment are still experiencing limitations in developing innovative, creative, and in accordance with the characteristics of students. The method used is an Action-Based Empowerment approach combined with Participatory Action Research (PAR) through training activities, mentoring, group discussions, traditional game modification practices, microteaching, and reflective evaluation. The results of the activity showed a significant improvement in all aspects measured. The pedagogic competence of Penjas teachers increased from 30% to 80%, the understanding of active learning in PJOK from 35% to 80%, the use of traditional games as learning media from 45% to 85%, traditional game modification techniques from 50% to 90%, and microteaching and evaluation skills from 40% to 93%. The average participant results increased from 40.0% in the pretest to 85.6% in the posttest. In addition, participants succeeded in producing various traditional game designs that have been modified and ready to be applied in learning. This activity has proven to be effective in improving pedagogic competence, creativity, and the ability of prospective teachers to develop student-centered active learning while supporting the preservation of local culture through the use of traditional games. Keywords: pedagogic competence, prospective service teachers, traditional games, active learning, learning media, creativity.